Q: What is 6x 11 12 5x?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

0. 6x + 3 = 5x + 141. 6x = 5x + 11 [subtracting 3]2. x = 11 [subtracting 5x]

6x + 3 = -7 -5x 6x + 5x = -7 -3 11x = -10 x = -10/11

One factor of 6x² + 5x - 11 is (x - 1).

5x - 3 + x - 9 = 5x Bring like terms together of the left side: 5x + x - 3 - 9 = 5x Combine like terms: 6x - 12 = 5x Add 12 to both sides: 6x = 5x + 12 Subtract 5x from both sides: x = 12

There can be no answer since there is no equation: only an expression. It is possible to factorise the expression as follows: 6x2 - 5x - 11 = 6x2 + 6x - 11x - 11 = 6x(x + 1) - 11(x + 1) = (x + 1)(6x - 11) Just to add, if you meant 6x2 - 5x - 11 = 0, then the above factorise would give you either (x+1) = 0, or (6x-11)=0, so x=-1 or 11/6

Related questions

0. 6x + 3 = 5x + 141. 6x = 5x + 11 [subtracting 3]2. x = 11 [subtracting 5x]

-5x+1 = 6x -5x-6x = -1 -11x = -1 x = 1/11

6x + 3 = -7 -5x 6x + 5x = -7 -3 11x = -10 x = -10/11

One factor of 6x² + 5x - 11 is (x - 1).

5x - 3 + x - 9 = 5x Bring like terms together of the left side: 5x + x - 3 - 9 = 5x Combine like terms: 6x - 12 = 5x Add 12 to both sides: 6x = 5x + 12 Subtract 5x from both sides: x = 12

There can be no answer since there is no equation: only an expression. It is possible to factorise the expression as follows: 6x2 - 5x - 11 = 6x2 + 6x - 11x - 11 = 6x(x + 1) - 11(x + 1) = (x + 1)(6x - 11) Just to add, if you meant 6x2 - 5x - 11 = 0, then the above factorise would give you either (x+1) = 0, or (6x-11)=0, so x=-1 or 11/6

6x + 5x = 11x

It is: 5x times 6x = 30x^2

6x - 3x = 5x - 10x + 12 6x - 3x - 5x + 10x = 12 8x = 12 8x/8 = 12/8 x = 12/8 = 3/2 x = 1.5

you say: 5x+7=84-6x 5x+6x+7=84-6x+6x 11x+7=84 11x+7-7=84-7 11x=77 x=77/11 x=7

-6x+3 = -7-5x 7+3 = 6x-5x 10=x

5x+15 = 6x-10 5x-6x = -10-15 -x = -25 x = 25